Accessibility of People With Disabilities to Work in Private Sector: Implementation of Public Policy towards Inclusive Society - Panji Hendrarso, (Technium Social Sciences Journal, 2021)
The research is aimed at answering the question of what difficulties are experienced by persons with disabilities in the accessibility of getting jobs and what efforts should be made to increase the absorption of employment for persons with disabilities in private companies. This research is a qualitative study with a phenomenological approach. Participants in this study were 30 people with disabilities who were categorized based on their educational backgrounds ranging from elementary, junior high, senior high, college to university graduates. The results of this study indicate that the implementation of policies for people with disabilities as outlined in Law Number 8 of 2016, Law Number 13 of 2003 concerning Manpower and Law Number 19 of 2011 served as Ratification of the CRPD (Convention on the Rights of Persons with Disabilities) pertaining to the rights of persons with disabilities in Article 27 concerning work and employment have not been fully implemented by private sector. This study also found that there are still many people with disabilities who receive discrimination in the form of refusal to work for companies even though they have already got skills and competencies as well as graduate degrees like other normal students. In order that this public policy to be implemented effectively, steps are needed, namely more intensive socialization, imposing sanctions for companies that refuse to employ people with disabilities and formulating awards for companies that employ more than 1% of people with disabilities as a stimulus for private companies in Indonesia.